Species diversity of thrips (Thysanoptera) in selected avocado orchards from Mexico based on morphology and molecular data - Daniel Bravo-Pérez; Ma. Teresa Santillán-Galicia; Roberto M. Johansen-Naime; Héctor González-Hernández; Obdulia L. Segura-León; Daniel L. Ochoa-Martínez; Stephanie Guzman-Valencia (Journal of Integrative Agriculture, 2018)
Avocado is one of the most important crops in the world, and Mexico is the largest producer of this fruit. Several insect pests affect its production, and thrips are amongst the most important. A key step in the design of control methods is accurate species identification. Despite this, formal reports on species diversity of thrips in Mexico are very scarce. Morphological identification can sometimes be time-consuming and inconclusive. Therefore, we explored the species diversity of thrips in Mexican avocado orchards (Michoacan state) based on partial sequences of the mitochondrial gene cytochrome oxidase subunit I (COI). Forty-four specimens were analysed, which represented approximately 8% of all individuals collected from five localities distributed in three Municipalities. All specimens were analysed using the COI marker, and specimens within the genera Frankliniella were also analysed using a marker within the D2 domain of the 28S (28SD2) nuclear ribosomal DNA. Molecular identifications were confirmed using morphological taxonomy. Overall, six genera were found (Neohydatothrips, Scirtothrips, Frankliniella, Arorathrips, Caliothrips and Leptothrips). All genera contained only one species, except Frankliniella, for which there were six species. Data from the two molecular markers suggest the existence of cryptic species within Mexican F. occidentalis populations.